Arteriovenous Vascular Access Selection and Evaluation - Jennifer M. MacRae; Matthew Oliver; Edward Clark; Christine Dipchand; Swapnil Hiremath; Joanne Kappel; Mercedeh Kiaii; Charmaine Lok; Rick Luscombe; Lisa M. Miller; Louise Moist (Canadian Journal of Kidney Health and Disease, 2016)
When making decisions regarding vascular access creation, the clinician and vascular access team must evaluate each patient individually with consideration of life expectancy, timelines for dialysis start, risks and benefits of access creation, referral wait times, as well as the risk for access complications. The role of the multidisciplinary team in facilitating access choice is reviewed, as well as the clinical evaluation of the patient.